Pengaruh Gaya Kepemimpinan Tranformasional dan Budaya Organisasi Terhadap Kepuasan Kerja Karyawan di PT. The Patra Bali - I Gusti Ngurah Madya Kertha Yasa; Ni Made Yusmini; Pande Putu Ida Yuliantari (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This study seeks transformational leadership style and organizational culture to impact employee satisfaction. Both the sample used and all employees of PT. Patra Bali are 72 people. In this study, the data analysis techniques used are multiple linear regression, coefficient of determination, t-test, and F-test. The results of the study indicate that transformational leadership style and organizational culture have a positive and significant effect on employee job satisfaction; transformational leadership style and organizational culture also have a positive and significant effect on employee job satisfaction. The researcher hopes that PT. Patra Bali will evaluate the leadership patterns that have been established, so that the company can implement the right leadership patterns in the future by always providing salaries according to employee performance and establishing salary policies according to employee work.